2021
DOI: 10.1177/09673911211042504
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of n-type polyaniline/hexagonal boron nitride composites with a large thermoelectric power factor

Abstract: In the present study, it was aimed to investigate the thermoelectric (TE) properties of polyaniline/hexagonal boron nitride (PANI/h-BN) composites. First, h-BN was synthesized from boric acid and urea. Then, PANI-HCl was synthesized by oxidative chemical polymerization. Finally, the composites were prepared using different weight ratios of h-BN. The composites were characterized using attenuated total reflection accessory attached Fourier-transform infrared spectroscopy, UV-vis spectroscopy, X-ray diffraction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…The formations of PIn, tBN and tBN/PIn were confirmed by UV–Vis analysis (Figure S1) and matched well with literature reports 31–33 . PIn displayed an absorption peak at 272 nm, which was assigned to π–π* transition 31 .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The formations of PIn, tBN and tBN/PIn were confirmed by UV–Vis analysis (Figure S1) and matched well with literature reports 31–33 . PIn displayed an absorption peak at 272 nm, which was assigned to π–π* transition 31 .…”
Section: Resultssupporting
confidence: 88%
“…The formations of PIn, tBN and tBN/PIn were confirmed by UV-Vis analysis (Figure S1) and matched well with literature reports. [31][32][33] PIn displayed an absorption peak at 272 nm, which was assigned to π-π* transition. 31 tBN was characterized by absorption maxima at 206 nm, and an absorption tail extending up to 800 nm.…”
Section: Uv-vis Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the intensity of the peak corresponding to the hydroxyl (OH) group detected at approximately 3220 cm –1 was increased by plasma treatment (Figure b,c). Additionally, the Ar/O 2 plasma treatment increased the intensity of the OH peak and led to the appearance of a new group as indicated by the B–N–O peak at 1200 cm –1 in Figure c. , To confirm the defect of the BNNT surface arising from the plasma treatment, we compared the relative areas of the B–N stretching mode, the B–N–O bend mode, and the OH stretching mode for the plasma-treated BNNTs and pristine BNNTs (Figure S1). The relative FT-IR peak area ratio of pristine BNNT consisted of 99.9% for B–N stretching and 0.1% for OH stretching.…”
Section: Resultsmentioning
confidence: 99%
“…49 Ugraskan et al reported that the addition of h-BN enhanced the thermoelectric performance of polyaniline (PANI)-HCl, and an optimum PF of 143.1 μW m −1 K −2 was obtained for BN@PANI-HCl. 50 However, to the best of our knowledge, exfoliated BN nanosheet (EBNS) doped SWCNT thermoelectric materials are rarely reported. The higher potential barrier at the interface between EBNS and SWCNT facilitates filtering low-energy carriers and enhancing the Seebeck coefficient.…”
Section: Introductionmentioning
confidence: 99%